The Mediating Role of Marital Online Monitoring in Relationship between Attachment Behaviors and Marital Satisfaction among Married Women - Hashem Bait Ghanemi; Amin Koraei; Mansour Sodani (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2023)
Aim and Background: Marital satisfaction is related to some psychological variables, including attachment behaviors; Therefore, the purpose of this research was to investigate the effect of attachment behaviors on women's marital satisfaction with the mediating role of online surveillance. Methods and Materials: The design of the current research is a correlation design of the structural equation modeling type, which was a multivariate correlation method. The statistical population in this research was all married women in Khuzestan province whose husbands used social networks. Using the non-discriminatory snowball sampling method, 350 married women with electronic literacy and familiar with using social networks were selected. Subjects responded to the scale of the modified version of the attachment behavior scale of Sandberg et al. 2012, the online surveillance scale of the modified version of Ellison 2007 and the marital satisfaction scale. SPSS version 27 statistical software and structural equation modeling using Amos version 24 software were used to evaluate the proposed model. Findings: The results of the findings showed that the direct effect of attachment behaviors on online marital supervision and the direct effect of online marital supervision on marital satisfaction is significant p<0.05. Also, the direct effect of attachment behaviors on marital satisfaction is significant p<0.05. The indirect effect of attachment behaviors on marital satisfaction through online surveillance is also significant p<0.05. Considering the significance of the effect of attachment behaviors on marital satisfaction in the model, it should be said that online surveillance plays a partial mediating role in the relationship between attachment behaviors and marital satisfaction. Conclusions: According to the findings obtained from the present research, it can be said that attachment behaviors through online surveillance have an effect on the marital satisfaction of married women.